IMPLEMENTATION OF LEARNING ON MANUFACTURING COMPOST FOR PSYCHOMOTOR DEVELOPMENT IN EARLY CHILDREN - Nada Fitri Salsabila; Muhammad Azam Muttaqin (Media Inovasi Pendidikan dan Publikasi, 2024)
This research aims to find out and understand the implementation of learning to make compost on the psychomotor development of young children. This research uses a descriptive qualitative method which is carried out by collecting data obtained using observation and interview techniques. Based on the research results, learning to make compost can provide benefits in holistic psychomotor development of young children so that children have knowledge and understanding from an early age through simple activities that can act and be responsible for their environment.